2011
DOI: 10.1111/j.1469-8986.2010.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

The reduced N1 to self‐generated tones: An effect of temporal predictability?

Abstract: Tones that are self-generated elicit a smaller N1 than externally triggered tones. Typically, however, self-generated tones are also more predictable in time than externally triggered ones. The present study investigated whether the attenuated N1 can be explained by predictability based on the temporal relationship between action and effect. Participants listened to tones that were self-generated by a key-press or preceded by a visual cue. The tones followed the key-presses or cues after a fixed (predictable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
86
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 49 publications
11
86
1
Order By: Relevance
“…Previous research has found decreased N1 amplitude with tones that are predictable in time (Sowman, Kuusik, & Johnson, 2012;Ford, Gray, Faustman, Roach, & Mathalon, 2007). A recent study investigated this more closely and found that temporal prediction is not the sole reason that N1 suppression occurs when a self-made tone is processed (Lange, 2011). Our study supports this as our consequent tones were at variable times in relation to the first event; however, we still found N1 suppression for temporally unpredictable tones.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous research has found decreased N1 amplitude with tones that are predictable in time (Sowman, Kuusik, & Johnson, 2012;Ford, Gray, Faustman, Roach, & Mathalon, 2007). A recent study investigated this more closely and found that temporal prediction is not the sole reason that N1 suppression occurs when a self-made tone is processed (Lange, 2011). Our study supports this as our consequent tones were at variable times in relation to the first event; however, we still found N1 suppression for temporally unpredictable tones.…”
Section: Discussionsupporting
confidence: 70%
“…Investigations into the prediction of consequences have focused on particular components of the sensory ERP. Reductions in the amplitude of the N1 component have been found for sensory effects caused by self-made actions (i.e., self-made effects; Bass, Jacobsen, & Schroger, 2008;Martikainen et al, 2005) in both the auditory domain (Hughes, Desantis, & Waszak, 2013;Knolle, Schroger, & Kotz, 2013;Baess, Horvath, Jacobsen, & Schroger, 2011;Lange, 2011;Aliu et al, 2009) and the visual domain (Gentsch, Kathmann, & Schutz-Bosbach, 2012;Gentsch & Schutz-Bosbach, 2011;Hughes & Waszak, 2011). Even greater decreases in amplitude have been found for selfmade consequences that were predictable compared with self-made effects that were not (Hughes et al, 2013;Knolle et al, 2013;Gentsch et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…First, it seems possible that the hypothetical contingency representation is not built up at the beginning of or over the course of the experiment (see also Lange, 2011), but it already exists: It is a general "expectation" that our actions should generate some kind of a sensory event in the environment. Whereas it is an intriguing possibility that N1 suppression reflects an innate readiness for capturing contingent action-effect relationships during interactions with the environment, in this study, such a "readiness" could also be brought about by extensive training through the widespread use of keypress-based interfaces in everyday devices.…”
Section: Discussionmentioning
confidence: 98%
“…Support for this possibility comes from a study which analyzed self-generated speech sounds (i.e., more complex stimuli) and found longer lasting attenuation effects (Houde et al, 2002). By contrast, it seems rather unlikely that the observed temporal shift was due to the relatively long 150 ms interval between response execution and outcome onset as a few earlier studies suggested that the attenuation effect was unaffected by response-outcome delays of up to 1000 ms, regardless of whether the onset of outcome presentation was predictable or not (Baess et al, 2011; Lange, 2011; SanMiguel et al, 2013). Finally it should be noted that the fronto-central ERP effect was accompanied by a reversed polarity effect at posterior electrodes.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, action outcomes are perceived to be attenuated and shifted in time compared to stimuli that are unpredicted or predicted by other stimuli rather than one’s own actions (Von Holst and Mittelstaedt, 1950; Weiskrantz et al, 1971; Blakemore et al, 1998; Haggard et al, 2002). This is a widespread phenomenon that has not only been assessed behaviorally but also neuro-physiologically using different techniques (Schafer and Marcus, 1973; McCarthy and Donchin, 1976; Martikainen et al, 2005; Aliu et al, 2009; Reznik et al, 2014; Timm et al, 2014), including a number of recent EEG studies (Lange, 2011; Desantis et al, 2012; Hughes et al, 2013a,b; SanMiguel et al, 2013; Mifsud et al, 2016; Timm et al, 2016). When outcomes are sounds as in most previous studies, the typical finding are reduced outcome-evoked ERP amplitudes within the latency range of the N1 and P2 components at fronto-central electrodes.…”
Section: Introductionmentioning
confidence: 99%